Biochemical characterization of Plasmodium falciparum dipeptidyl aminopeptidase 1 - Wang, Flora (2010)
Dipeptidyl aminopeptidase 1 (DPAP1) is an essential food vacuole enzyme with a putative role in hemoglobin catabolism by the erythrocytic malaria parasite. Here, the biochemical properties of DPAP1 have been investigated and compared to those of the human ortholog cathepsin C. To facilitate the characterization of DPAP1, we have developed a method for the production of purified recombinant DPAP1 with properties closely resembling those of the native enzyme. Like cathepsin C, DPAP1 is a chloride-activated enzyme that is most efficient in catalyzing amide bond hydrolysis at acidic pH values. The monomeric quaternary structure of DPAP1 differs from the homotetrameric structure of cathepsin C, which suggests that tetramerization is required for a cathepsin C-specific function. The S1 and S2 subsite preferences of DPAP1 and cathepsin C were profiled with a positional scanning synthetic combinatorial library. The S1 preferences bore close similarity to those of other C1-family cysteine peptidases. The S2 subsites of both DPAP1 and cathepsin C accepted aliphatic hydrophobic residues, proline, and some polar residues, yielding a distinct specificity profile. DPAP1 efficiently catalyzed the hydrolysis of several fluorogenic dipeptide substrates; surprisingly, however, a potential substrate with a P2-phenylalanine residue was instead a competitive inhibitor. Together, our biochemical data suggest that DPAP1 accelerates the production of amino acids from hemoglobin by bridging the gap between the endopeptidase and aminopeptidase activities of the food vacuole. Two reversible cathepsin C inhibitors potently inhibited both recombinant and native DPAP1, thereby validating the use of recombinant DPAP1 for future inhibitor discovery and characterization.